Experimental investigation on thermal runaway propagation of large format lithium ion battery modules with two cathodes. (June 2021) - Huang, Zonghou; Li, Xin; Wang, Qingshan; Duan, Qiangling; Li, Yan; Li, Lina; Wang, Qingsong
Highlights: The TR propagations of the large-format NCM and LFP modules are compared. The critical parameters of TR propagation for both NCM and LFP modules are analyzed. The toxicity of ejected gases from NCM module is greater than that of LFP module. Abstract: LiNix Coy Mnz O2 (NCM) and LiFePO4 (LFP) batteries are the two most widely employed in vehicles and energy storage stations, however, fire accidents related to them occurs frequently. A comparative analysis on the thermal runaway (TR) propagation behavior of NCM and LFP module are conducted in this work. Results indicate that intense jet fire and combustion behavior occurs in the NCM module, only a considerable amount of white smoke is observed in the LFP module. Generally, the duration time ( td ) of TR and the maximum temperature ( Tmax ) of the NCM LIB are significantly higher than those of the LFP LIB. Compared with NCM modules, LFP modules are significantly less likely to suffer from TR propagation. Once TR propagation occurs in LFP module, the TR propagation in a single LFP LIB and LFP module is less aggressive and risk than in the NCM LIB and NCM module, respectively. And the TR propagation mechanism of the LFP and NCM modules are comparatively analyzed. Besides, the comparative analysis of gas production and gas toxicity of large format NCM and LFP module during TR propagation is revealed for the first time, which is very meaningful for the further evacuation and rescue of large-format LIB fires. It is found that the total mass of ejected combustible gases (including H2, CH4, C2 H4, C3 H6, CO) per failed cell number of the NCM module are much higher than that of the LFP module, which is determined to be 21.09 g and 4.17 g for the NCM and LFP module, respectively. Besides, the results calculated by the FED and FEC models demonstrate that the toxicity of ejected gases from NCM module is greater than that of the LFP module. This work present in detail the TR propagation characteristics of large-format NCM and LFP modules, which can provide valuable information for the safety design of lithium-ion batteries.